EFEKTIVITAS BANTUAN LANGSUNG TUNAI DANA DESA BAGI MASYARAKAT TERDAMPAK COVID-19 DI DESA KEKAIT - Dediantari Mas Maheswary; Herlina Pusparini; Aditya Bayu Suryantara (Jurnal Aplikasi Akuntansi, 2022)
In early 2020, the world was shocked by the outbreak of a virus originating from Wuhan, Tingkok, namely the Corona Virus (SARS-CoV-2) or called Covid-19. The Covid-19 pandemic has had a very significant impact on the world, including in Indonesia. The impact of this pandemic caused the country's economy to decline. Responding to this situation, the Indonesian government issued various assistance programs, one of which is the Village Fund Cash Direct Assistance (BLT-DD) program aimed at underprivileged villagers and of course based on the criteria of beneficiaries that have been set by the government. The purpose of this study is to find out the effectiveness of direct cash assistance of village funds for people in Kekait Village, especially for underprivileged communities, it is felt to be very beneficial for them. The author uses effectiveness theory according to Duncan with qualitative research methods of case study research types by conducting observations, interviews, questionnaires, and documentation. From the research that the author conducted, it shows that the implementation of the BLT-DD program in Kekait Village has been running effectively.